A new species of Chaceon Manning & Holthuis, 1989, from the southwestern Atlantic, with a key to the western Atlantic species (Crustacea, Decapoda, Geryonidae) - Tavares, Marcos; Pinheiro, Allysson P. (Zootaxa, 2011)
A new species of the deep-water crab genus Chaceon Manning & Holthuis, 1989 (Geryonidae Colosi, 1923), is described from southwestern Atlantic. It is the ninth species of the genus known from the western Atlantic. It is most closely related to C. eldorado Manning & Holthuis, 1989, C. notialis Manning & Holthuis, 1989, and C. ramosae Manning, Tavares & Albuquerque, 1989, from which it can be readily differentiated in having the dactyli of P2-P5 laterally compressed, instead of being dorsoventrally depressed. A key to the western Atlantic species of Chaceon is provided.